Reaksi Investor Dalam Pasar Modal Terhadap Penerbitan Perppu No. 1 Tahun 2017” - Anggariani, I Gusti Ayu Ade; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2018)
Perppu Number 1/2017 is one of the information that can be used to analyze market reaction. The purpose of this research is to prove empirically the existence of abnormal return and trading volume activity significant around the bookkeeping Perppu Number 1/2017. This research is research event study. The sample used 42 banking companies listed on the BEI with purposive sampling method. The analysis tool used is one sample t-test. The results showed that there was significant abnormal return at t -1 and t +2 , then trading volume activity volume was significant at t -2 , t -1 , t 0 , t +1 , t +2 . In the future, investors should consider information from Perppu Number 1/2017 when the application is done in 2018 to make investment decisions in order to gain profit.